Jaffna ‘Odiyal Koozh’ a Hidden Treasure of Palmyrah - Menaka, S. (University of Sri Jayewardenepura, 2019)
Palmyrah (Borassusflabellifer) is a nature’s gift to the Northern Province of Sri Lanka and the economical crop gives livelihood to the residents due to its food and nonfood values. Palmyrah tuber (odiyal) is an edible shoot and a good source of dietary fiber and calcium for human health. As a backbone of traditional Jaffna cuisine ‘Odiyal koozh’, a nutritional seafood soup made with palmyrah tuber flour. Traditional foods have nutritional aspects as well as they tie up the childhood memories and heritage. The study was conducted with the objective of recollecting the connection of ‘odiyal koozh’ with culture. Interviews, demonstrations and group discussions were carried out among local elders who are experts in making ‘koozh’, staff from restaurants which serve ‘koozh’ in their menu and immigrants to Europe countries during their visit to Jaffna in the period of July to August 2018 . From the field observations and discussion it was found that the ‘koozh’, a display of one’s culinary skill is not only a food but it fills the gap between the generations.A rich combination of freshly caught fish, prawns, crabs and cuttlefish with the choice of long beans, manioc, chilli, drumstick, leaves, parboiled rice, tamarind, jack seeds odiyal flour is prepared in earthenware. The hot and spicy ‘koozh’ is served with coconut kernels in natural eco-friendly vessels made from spiky palmyrah leaves called as ‘pila’ or coconut shells and folded jack leaves are used as spoons.The signature dish of Jaffna gives better nourishment of protein, fiber, minerals and vitamins which gave longevity for the ancestors.The preparation is considered as a center for gathering of relatives and friends to share the culinary tradition. Along with heightening the traditional experience elders said that ‘koozh’ is a serious killer of cold flu during their childhood.The respondents felt that the tradition is slowly disappearing due to the busy life style and nuclearization of families as ‘koozh’ is prepared mostly when the immigrants who know the values of heritage visit their home lands. People can taste a delicious bowl of ‘koozh’ in restaurants but the traditional cultural identity and heritage cannot be purchased with any cost there.
Keywords: odiyal; ‘koozh’; Palmyrah; Jaffna culture; Heritage